KONSEP KEMASLAHATAN MAQĀṢĪḌ SYARĪAH IBNU ‘ASHUR TERHADAP PERMASALAHAN DI ERA MILENIAL: Polemik Kebijakan Lockdown dan PSBB Pemerintah Indonesia dalam Menangani Pandemi Covid-19 - Inama Anusantari (Fakultas Syariah (Syari'ah Faculty ), 2021)
As a scholar, Ibn ‘Ashur a prolific scholar. One of this famous works is about Maqashid Syariah. Where in this heory contains the concept of mashlahah which is considered in accordance with the times. One of the problems in the millennial era that is being faced by the world community, especially Indonesia is the Covid-19 pandemic. To deal with the Covid-19 pandemic, the government has established a PSBB policy. It is not the lockdown policy tha most parties have been promoting. The purpose of this paper is to find out the concept of mashlahah in the theory maqashid syariah Ibnu ‘Ashur regarding the Covid-19 polemik of the Indonesian government’s lockdown and PSBB policies in the face of the Covid-19 pandemic. The method in this writing uses a research library that is deductive to analysis, where data is collected and then describes the data. Sources of data in this paper are in the form of scientific journals, books, online articles anda Indonesian Government Regulation related ti the theme. Data Collection techniques with documentation techniques. The results showed that in determining the benefit of law, Ibn ‘Ashur used a more philosophical approach. By examining the purpose of the legal text the looking for its arguments. In facing problems in the millennial are, the concept of kemashlahatan Ibn ‘Ashur’s maqashid sharia theory is still very relevant.